The Influence of Human Resource Competence, Level of Education and Use of Information Technology on the Quality of Financial Reporting Village Credit Institutions in Abiansemal District, Badung District - Cempaka Dewi, Ni Wayan; Yadnyana, I Ketut (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
Good quality financial reports are financial reports that can produce useful information in making economic decisions. Educated human resources play an important role in preparing financial reports by utilizing information technology will assist in the preparation of financial statements. The purpose of this study was to analyze the effect of human resource competence, level of education and the use of information technology on the quality of the financial reports of the Village Credit Institution in Abiansemal District, Badung Regency. This research was conducted in all LPDs in Abiansemal District, the number of samples used was 96 respondents with the saturated sampling method (census method). The data collection used in this research is a questionnaire. The collected data was then analyzed using Multiple Linear Regression analysis. The results of this study indicate that HR competence has a positive and significant effect on the quality of LPD financial reports in Abiansemal District. Education level has a positive and significant effect on the quality of LPD financial reports in Abiansemal District. The use of information technology has a positive and significant effect on the quality of LPD financial reports in Abiansemal District. The implication of this research is that human resource competence and education level play an important role in the process of preparing LPD financial reports for quality results in the preparation of LPD financial reports and by utilizing information technology optimally it will produce good and quality financial reports.